Konstruksi Makna Keteladanan dalam Maulid Al-Barzanji Bab XVIII Karya Syaikh Ja’far Al-Barzanji: Kajian Struktural dan Intertekstual - Muzammil Muzammil; Ade Kosasih; Ikhwan Ikhwan (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study examines how Maulid Al-Barzanji Chapter XVIII constructs the meaning of exemplary conduct (keteladanan) of Prophet Muhammad through its literary structure and intertextual network. Using a descriptive-qualitative method with structuralist and intertextual approaches (Kristeva and Genette), the study analyzes the text’s thematic architecture and its transformative relationships with classical Islamic sources including al-Shamāʼil al-Muḥammadiyyah, al-Sīrah al-Nabawiyyah, and authenticated hadith. The findings reveal that each faṣīlah functions as a rhetorical unit that not only conveys prophetic virtues, simplicity, social care, forgiveness, moral courage, and spirituality, but systematically constructs them into a unified moral argument. Intertextual analysis demonstrates that Al-Barzanji does not merely reproduce his sources; he transforms narrative-descriptive material into poetic-reflective devotional literature. This aesthetic transformation is the mechanism by which the text produces meaning beyond information transfer. The study concludes that Maulid Al-Barzanji Chapter XVIII functions as a model of Islamic literary adaptation: a classical genre that encodes prophetic exemplarity through the interplay of structure and intertextuality.